O impacto das novas tecnologias sobre as competências profissionais da geração baby boomer - Rosso, Leila Urioste (2015)
This study reflects on the influence of new technologies on the professional skills of workers born between the years 1945 and 1967, belonging to the so-called baby boomer generation. Justified the choice of the baby boomer generation as this is the group of people who are no longer in the labor market, and are living the changes by the presence of new information and communication technologies in the workplace, having to adapt since it is a very different context than when they started their professional careers. The research problem of this study is presented as follows: the influence of new technologies on the development of professional skills of the baby boomer generation? What this generation had to develop skills to maintain and adapt to new demands of the labor market? The general objectives aimed at promoting an analysis about building the skills of workers in the Baby Boomer generation on the context of new technologies and show how was the organization of work and what professional skills employed at the beginning of this activity. The methods used in this study were the Library Research and the Research called Life History. Semi-structured interviews were used with the application of a previously prepared script. It was found that the maturing of the revolution of information technology in the 1990s transformed the work process, introducing new technical and social division of labor, so that the workers of the baby boomer generation develop different skills from those applied in the method productive Taylor / Ford. This is a generation that learned and started working with Fordism / Taylorism and some in the middle of their careers, they had to adapt to Toyotist mode of production, based on teamwork, systemic vision in the process work (and no longer on the task), and the entrepreneurship of their own careers